hubungan pengetahuan dan sikap dengan perilaku ibu dalam pencegahan karies gigi pada anak - Maria Lusi; Nursefa Arief Hermawan (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2021)
The  prevalence  of dental caries in children aged 5-9 years in Indonesia in 2018 is 92.6%. The proportional of dental  and  oral problems in children aged  5-9 years in  Lampung Province is 67.0%. In  Bandar Lampung city the most common amounting to 82%. UKS Data at Way Kandis Public Health Center in 2018, at SD Negeri 3 Way Kandis there were 90% of students with cases of dental caries and rarely brushed their teeth. objective was to know correlation between knowledge and attitudes with mother's behavior  in preventing dental caries in children  at SDN 3 Way Kandis Bandar Lampung city in 2020. This  was  an analytic  research  with cross  sectional  approach. Samples were all mothers who had school-age children with good dental health and studied. at SDN 3 Way Kandis Bandar Lampung cityi in June 2020 with a total sampling techniquequse of 38 people.The  research  result   a significant between knowledge with Dental Caries Prevention Behavior (p-value = 0.011, OR = 7.792)., There was  a significant correlation between attitude with dental caries, prevention  behavior at SDN 3 Way Kandis Bandar Lampung 2020 (p-value = 0.004, OR  =  10.400).  It is  necessary to  add information   about  the benefits  of preventing   dental  caries in  school-age , children in mothers with school-age children who are at SDN 3 Way Kandis Bandar Lampung by  distributing  leaflets  on how to prevent dental  caries in school-age , children and practice how to brush  teeth properly and true in school so that mothers get the latest information that can change the attitudes of mothers about dental caries prevention behavior, in the end it will reduce the incidence of dental caries in school-age children at SDN 3 Way Kandis Bandar Lampung City.